Soundscapes show disruption across the diel cycle in human modified tropical landscapes. (November 2022) - Lawson, Jenna; Whitworth, Andrew; Banks-Leite, Cristina
Highlights: The characteristic dawn and dusk chorus are lost or supressed in tropical plantation forestry. Restricting soundscape analysis to narrower temporal windows masks both temporal and spatial differences among habitat types. Acoustic activity during dawn and dusk is reduced in disturbed ecosystems compared to healthy native forest ecosystems." Abstract: 1. Fluctuations in the diel cycle, especially when compared across different land-use types, can reveal key changes in acoustic activity and the biological community. Yet few studies have assessed the effects of land use change on soundscapes across the diel cycle. The emergence of passive acoustic monitoring (PAM) allows us to monitor landscapes over longer and continuous periods, providing data on temporal variability across the diel cycle. 2. Using AudioMoth acoustic recorders we collected data at 120 sites on the Osa Peninsula, Costa Rica, across a gradient of land use intensity. Information was extracted from recordings using a suite of nine acoustic indices. Principal component analysis reduced the indices into two axes, the first reflecting acoustic activity in the mid frequency bands, where the majority of biotic sound is present, and the second, representing acoustic activity in the upper frequency bands and the ratio of activity between the lower and mid-frequency bands. 3. In disturbed land use types we found reduced acoustic activity during the characteristic dawn and dusk peaks in the diel cycle; known as the dawn and dusk chorus. Palm oil plantations showed a complete loss of these peaks, while teak plantations retained evidence of a weaker dawn and dusk chorus. Restricting the analysis to narrower temporal windows masks these differences among habitats. 4. Synthesis and applications. Evaluating acoustic diversity at specific times of the day, which is common practice in bioacoustics studies, may be misleading, as pronounced changes in acoustic activity at dawn and dusk were obscured. By assessing trends across the diel cycle, we can gain a much better representation of the changes in acoustic activity. Our results show that in disturbed ecosystems there is a deviation in acoustic activity from that seen in a healthy native forest ecosystem, suggesting that there are likely changes within the biotic community in these ecosystems.